Inclusive Growth in Iran's Provinces (2004 -2015) - Seyed Hossein Mirjalili; Amin Mohseni Charaghlou; Omid Safari (International Journal of Business and Development Studies, 2017)
This paper aims to focus on inclusive growth and its impact on multidimensional poverty and inequality in Iran's provinces on the basis of social mobility index. The results suggest, that although the multidimensional poverty has decreased, participation of active labor force has a decisive role in inclusive growth and reduction of absolute multidimensional poverty of the provinces. But labor participation has been accompanied by inequality of income, which indicates that the opportunity for economic growth has been unevenly distributed, as higher income deciles have more benefits. Income inequality has moderated the positive and significant effect of GDP growth on its inclusiveness. Inflation also has a negative and significant effect on the inclusive growth of the provinces. The research findings indicate that the economic and financial policies, including the ratio of bank credit to GDP and government social expenditures, have a positive and significant effect on the acceleration of inclusive growth and have been able to generate inclusive, albeit unsustainable growth in the provinces. This inclusive growth has led to a reduction in poverty and inequality. However because of its volatility and instability, it has no significant impact on poverty and inequality and did not directly reduce poverty and inequality in the provinces.
Keywords: 330; Inclusive Growth; Multidimensional Poverty; Income Inequality in Iran's Provinces; Systemic Generalized Moment